A Systematic Literature Review on the Concept of Evacuation Route Planning and Assembly Points for Public and Residential Areas - Septiansyah, Adeka; Wismadi, Arif (Journal La Sociale, 2026)
Evacuation routes are a vital element in regional planning, particularly in densely populated urban areas prone to earthquakes and fires. High-density areas often face constraints such as limited space, poor road connectivity, potential congestion, and minimal disaster risk mapping. This complexity increases when comparing heterogeneous public areas with residential areas with a more homogeneous social character. This study aims to trace the development of evacuation route and assembly point planning concepts and identify their correlations through bibliometric mapping. The method used is a Systematic Literature Review (SLR) of international and national journals published in the last 10 years. The study results identified four main concepts: participatory, risk perception, agent, and activity. Of these, the participatory and risk perception concepts are considered the most relevant. The risk perception concept is effectively applied in public areas to increase awareness and preparedness, while the participatory concept is appropriate in residential areas because it directly involves the community in planning. The integration of the two is expected to produce an evacuation strategy that is adaptive, applicable, and oriented towards public safety.